Pro Microsoft Hyper-V 2019 practical guidance and hands-on labs - Syrewicze, Andy; Siddaway, Richard (Apress, 2018)
Successfully create and manage your Hyper-V environment without any of the marketing fluff. This book's lab-driven, hands-on approach will get you up and running as quickly and efficiently as possible. Virtualization is the cornerstone of today's data center. As a modern-day IT pro, you are required to manage environments that are in a regular state of flux and increasing in both size and complexity. To keep up, you need practical information in a format that is succinct, yet comprehensive and highly applicable. Pro Hyper-V 2019 breaks down critical and time-saving topics into a series of easy-to-digest chapters, showing you how to perform Hyper-V management tasks using both GUI and PowerShell-based tools. Building on your existing knowledge of Windows Server management, Active Directory, networking, and storage, experts and Microsoft MVPs Syrewicze and Siddaway begin with a foundation of why computing workloads are virtualized. This is followed by chapters covering the range of management tasks associated with virtualized environments, including: managing hosts and guest machines; networking, storage, and high availability (host and guest); disaster recovery and virtual machine migration; and monitoring. What You'll LearnApply practical information to administer your Hyper-V environmentsUnderstand multiple administration styles (GUI, command line, and automation)Written by IT pros for IT pros - just the information you really need without the paddingAdminister and use containersUtilize hands-on labs to learn about storage, networking, and high availability Who This Book Is For IT administrators tasked with implementing Hyper-V environments or migrating from VMware. IT pros joining a team that is responsible for managing Hyper-V and "lone administrators" covering the gamut in smaller organizations will also find this book indispensable
Online resource; title from PDF title page (EBSCO, viewed November 6, 2018)
Keywords: Microsoft Windows server Hyper-V; Virtual computer systems; Systèmes virtuels (Informatique); Microsoft programming; COMPUTERS; Operating Systems; Windows Server